(untitled) (Research, Society and Development, 2022)
The floodplain areas comprise the floodplains influenced by white water rivers, rich in sediments. The beginning of the process of occupation of floodplain areas in the Amazon is strongly debated by scholars and researchers. Some authors point out that the occupations occurred in a diffuse way in the Amazon, predominating in two large environments in the Amazon, the terra firme forests and the forests in floodplain areas. These characteristics boosted four main economic activities in the floodplain: fishing, forestry, agriculture and livestock. These activities were, for a long time, practiced by indigenous people and soon followed by caboclos-ribeirinhos, respecting the limits of nature and its carrying capacity. However, over the years and with the advent of modernity, it has not only projected the growth of man, and his reason, but has also increased the exploitation of natural resources used by man. Fishing resources such as arapaima, manatees and turtles, in addition to multispecific fishing, acquired another character with the arrival of the Portuguese, which persists to this day. In this way, it is clear how these resources are becoming scarce due to irrational use and above all marketing.